Fenomena Tren Hijrah Keberagaman di Kalangan Gen Z: Studi Fenomenologi Kecenderungan terhadap Corak Dakwah Sufisme dan Salafisme - Yuminah Rahmatulloh; Muhammad Iqbal; Ahmad Fardan; Safry Rahmatullah (Jurnal Budi Pekerti Agama Islam, 2025)
The phenomenon of religious hijrah (spiritual migration) among Generation Z (Gen Z) has emerged as a noteworthy social trend in recent years. This study aims to explore the religious tendencies of Gen Z through a phenomenological approach, focusing on two prominent currents of Islamic preaching: Sufism and Salafism. Employing a qualitative method, in-depth interviews were conducted with selected Gen Z individuals actively engaged in Sufi- and Salafi-oriented preaching communities. The findings reveal that their choice of religious orientation is not solely influenced by theological aspects, but also shaped by social, psychological, and personal spiritual factors. Sufism tends to appeal to those seeking inner peace and spiritual experience, while Salafism attracts individuals who yearn for religious certainty and a firm Islamic identity. These results reflect the complex and diverse nature of Gen Z’s religiosity, emphasizing the need for contextual and humanistic preaching strategies. This study hopes to contribute to a deeper understanding of young Muslims' religious patterns and the development of more relevant da'wah approaches in the digital age.